Ternary chalcogenide composite perovskite catalytic material as well as synthesis method and application thereof
By constructing the S-shaped heterojunction of AgIn5S8 and LaMnO3, the charge recombination and photocorrosion problems of single-component photocatalysts are solved, and efficient and stable photocatalytic degradation effects are achieved, especially the effective degradation of organic pollutants such as bisphenol A under visible light conditions.
Patent Information
- Application Number
- CN202510889707.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-30
- Publication Date
- 2025-07-29
- Estimated Expiration
- 2045-06-30
AI Technical Summary
The existing single-component AgIn5S8 photocatalysts have problems with rapid charge recombination, low quantum efficiency and photocorrosion during the photocatalytic degradation process, resulting in poor results in practical applications. The narrow band gap of LaMnO3 leads to a high carrier recombination rate, limiting its photocatalytic activity.
By constructing the S-shaped heterojunction of AgIn5S8 and LaMnO3, the energy band structure matching between the two is used to form the AgIn5S8/LaMnO3 composite material, the charge separation and transmission efficiency are enhanced, the electron-hole pair recombination is reduced, and the photocatalytic activity is improved.
It realizes efficient degradation of pollutants under visible light irradiation, generates a variety of active oxidizing substances, improves the stability and reusability of the photocatalyst, and enhances the degradation ability of organic pollutants.
Smart Images

Figure CN120381854A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of photocatalysts, and particularly relates to a ternary chalcogenide composite perovskite catalytic material, a synthesis method thereof, and an application thereof. Background Art
[0002] In the field of photocatalysis, various types of semiconductors have been used to remove organic pollutants in aqueous media. For this purpose, an increasing number of photocatalysts have emerged, such as bismuth-based photocatalysts, silver-based photocatalysts, phosphorus-based photocatalysts, titanium dioxide-based photocatalysts, cadmium sulfide-based photocatalysts, peroxide-based photocatalysts, metal-organic framework-based photocatalysts, g-C3N4-based photocatalysts, and so on. In recent years, ternary doped semiconductor materials have been widely applied in the environmental and energy fields related to photocatalysis. Among them, AgIn5S8 has a relatively wide solar absorption range (~700 nm) due to its narrow bandgap (1.70 - 1.80 eV), and is a potential visible light-responsive photocatalyst. However, for single-component AgIn5S8, its rapid charge recombination, low quantum efficiency, and inevitable photocorrosion make it difficult to achieve application. The degradation performance of photocatalysts mainly depends on charge separation and transfer. In addition, the oxidation ability of photocatalysts is also restricted by their energy band positions, and the energy band positions have an important impact on the mineralization degree and biodegradability of pollutants. Therefore, simultaneously improving the ability of charge separation and generating oxidation species (hydroxyl radicals, superoxide radicals, sulfate radicals, singlet oxygen, etc.) is crucial for photocatalytic degradation and mineralization of organic pollutants.
[0003] Among various strategies, constructing heterojunctions in photocatalysts can improve the feasibility and effectiveness of spatial separation of electron-hole pairs, and is proven to be one of the methods for modifying photocatalysts. Appropriately designing the spatial potential difference between semiconductors with matching energy band structures and electron energy levels can accelerate the separation and transfer of photo-generated electron-hole pairs, expand the spectral response range, and significantly improve the photocatalytic activity and photochemical stability of heterojunction photocatalysts.
[0004] Lanthanum manganite (LaMnO3), as a typical ABO3-type perovskite structure and a native p-type semiconductor, is theoretically and experimentally proven to be an effective photocatalyst, showing unique physical and chemical properties in the fields of photocatalytic water oxidation and degradation of organic pollutants, and having the characteristics of low cost and environmental friendliness. In addition, due to its Mn 4+ ↔Mn 3+The reversible reduction performance of [substance name] makes it a candidate catalyst for heterogeneous catalytic processes. However, the narrow bandgap of LaMnO3 leads to a relatively high carrier recombination rate, limiting its utilization in photocatalytic processes. Therefore, coupling LaMnO3 with different semiconductors and tuning the band potential are considered effective ways to hinder the recombination rate and improve photocatalytic activity. The valence band position of LaMnO3 is ~1.95 eV, and the conduction band position is 0.01 eV. The valence band position of AgIn5S8 is approximately 1.01 eV, and the conduction band position is approximately -0.72 eV. The band positions of the two enable LaMnO3 and AgIn5S8 to theoretically match well to form a heterojunction.
[0005] Therefore, the present invention develops a ternary chalcogenide composite perovskite catalytic material and synthesizes an AgIn5S8 / LaMnO3 S-type heterojunction to photocatalytically degrade the pollutant bisphenol A under visible light irradiation. Summary of the Invention
[0006] The object of the present invention is to provide a synthesis method of a ternary chalcogenide composite perovskite catalytic material, which can prepare a ternary sulfide composite perovskite catalytic material with stronger visible light absorption, higher charge separation efficiency, better stability, reusability, and capable of photocatalytically degrading organic pollutants by a simple process.
[0007] Another object of the present invention is to provide a ternary chalcogenide composite perovskite catalytic material.
[0008] Another object of the present invention is to provide an application of a ternary chalcogenide composite perovskite catalytic material.
[0009] The technical solution of the present invention is as follows: (I) A synthesis method of a ternary chalcogenide composite perovskite catalytic material, characterized by comprising the following steps: A. Add silver nitrate and indium chloride to absolute ethanol and continuously stir for 15 - 30 min, then add thioacetamide and continue stirring for 15 - 30 min. Subsequently, subject this solution to a hydrothermal reaction. After the reaction is completed, cool it to room temperature, centrifuge to collect the obtained product, wash it, and then dry it to constant weight to obtain the material AgIn5S8; B. Dissolve AgIn5S8, MnCl2·4H2O, and citric acid in distilled water and continuously stir for 15 - 30 min, then add La(NO3)3·6H2O and continue stirring for 15 - 30 min. Heat this solution and continuously stir until a gel-like precursor is obtained. Subsequently, conduct a hydrothermal reaction. After the reaction is completed, wash it, filter it, and dry it to constant weight. Finally, calcine the obtained composite material and let it cool naturally to obtain the catalytic material AgIn5S8 / LaMnO3.
[0010] As a further improvement of the present invention, in step A, the molar ratio of silver nitrate, indium chloride, and thioacetamide is 1:2.5 - 5:4 - 8.
[0011] As a further improvement of the present invention, in step A, the temperature of the hydrothermal reaction is 160 - 200 °C, and the time of the hydrothermal reaction is 20 - 24 h.
[0012] As a further improvement of the present invention, in step B, the mass ratio of AgIn5S8, MnCl2·4H2O, citric acid, and La(NO3)3·6H2O is 100:16.8 - 33.6:31.7 - 63.4:34.7 - 69.4.
[0013] As a further improvement of the present invention, in step B, the heating temperature is 70 - 80 °C, and the continuous stirring time is 5 - 10 min.
[0014] As a further improvement of the present invention, in step B, the temperature of the hydrothermal reaction is 180 - 240 °C, and the time of the hydrothermal reaction is 16 - 20 h.
[0015] As a further improvement of the present invention, in step B, during calcination, the heating rate is 2 - 10 °C / min, the calcination temperature is 600 - 800 °C, the calcination time is 3 - 5 h, and the atmosphere is air. (II) A ternary chalcogenide composite perovskite catalytic material is prepared by the synthesis method of the above ternary chalcogenide composite perovskite catalytic material.
[0017] AgIn5S8 is a ternary chalcogenide, and LaMnO3 is a perovskite material. They have similar band gaps, which are 1.74 eV and 1.94 eV respectively. This means that a single material can capture the vast majority of visible light. However, the narrow band gap leads to a relatively high recombination rate of bulk carriers in both materials. AgIn5S8 and LaMnO3 have a matching energy band structure. Therefore, when the two are combined, the matching energy level structure can transfer the photo-generated electrons of LaMnO3 across the heterojunction interface to AgIn5S8, reducing the recombination of electron-hole pairs, greatly enhancing the spatial interface charge transfer efficiency. The synergistic effect of the two together enhances the visible spectrum absorption. The existence of the heterojunction makes up for the unreasonable problem of the energy band positions of each other, effectively improving the light trapping and spatial interface separation efficiency, enabling the S-type heterojunction material to efficiently degrade pollutants under visible light irradiation, and having the characteristics of good stability in the aqueous phase and recyclability. (III) An application of a ternary chalcogenide composite perovskite catalytic material in photocatalytic degradation of pollutants.
[0019] Furthermore, the pollutants include bisphenol A, and also include atrazine, carbamazepine, tetracycline, rhodamine b, etc. Preferably, the AgIn5S8 / LaMnO3 of the present invention has particularly excellent degradation effect on bisphenol A under photocatalytic conditions. On the one hand, the photocatalytic material AgIn5S8 / LaMnO3 is photoexcited under visible light irradiation to generate photogenerated electrons and photogenerated holes. The matching energy level positions enable the photogenerated electrons in the conduction band of LaMnO3 to transfer across the heterojunction interface to the valence band of AgIn5S8. This S-type charge transfer mechanism not only promotes the separation of carriers, but also retains strong redox ability and promotes the transfer of space charge. On the other hand, in the presence of a polarization electric field, the generation of photogenerated electron-hole pairs on the surface of the LaMnO3 material is further induced continuously, significantly improving the charge separation efficiency.
[0020] The beneficial effects of the present invention are as follows: The ternary chalcogenide AgIn5S8 and the perovskite material LaMnO3 have narrow band gaps and good visible light absorption. However, both pure-phase single materials face the problems of rapid charge recombination and photocorrosion, resulting in low activity. The present invention composites AgIn5S8 and LaMnO3 by constructing a heterojunction to construct an S-type heterojunction catalytic material with stronger charge separation ability, light absorption range covering the entire visible spectrum, and higher catalytic activity - AgIn5S8 / LaMnO3. The traditional single-component AgIn5S8 and LaMnO3 have good visible light absorption, but the narrow band gap means faster in-situ recombination of carriers. They have staggered energy band structures with each other. By constructing a heterojunction, AgIn5S8 and LaMnO3 are composite, and the separation of photogenerated electron-hole pairs of the AgIn5S8 / LaMnO3 composite photocatalytic nanomaterial at the heterojunction interface is successfully realized, avoiding the electron-hole recombination problem in the band gap of a single nanomaterial. The matching energy level position arrangement enables the two to accelerate the migration and separation of photogenerated charges. By constructing the S-type heterojunction, under visible light irradiation, the photogenerated electrons of LaMnO3 can transfer across the heterojunction interface to AgIn5S8, reducing the recombination of electron-hole pairs in their bulk phases, more effectively enhancing the charge separation and electron transfer at the heterojunction interface, and greatly improving the photocatalytic activity. At the same time, it makes up for the unreasonable problem of the energy band position of a single material. Finally, the AgIn5S8 / LaMnO3 photocatalytic system realizes effective pollutant degradation. After being excited by visible light, it reacts with water molecules and dissolved oxygen to generate various types of active oxidation substances to efficiently degrade pollutants in the aqueous phase. The present invention has the characteristics of simple synthesis method, good stability, and recyclability. Description of the Drawings
[0021] Figure 1 It is the scanning electron microscope image of AgIn5S8 / LaMnO3 prepared in Example 1 of the present invention; Figure 2 UV diffuse reflectance absorption spectra of AgIn5S8 / LaMnO3, AgIn5S8, and LaMnO3 prepared in Example 1 and Comparative Examples 1 and 2 of the present invention; Figure 3 Fourier transform infrared spectra of AgIn5S8 / LaMnO3, AgIn5S8, and LaMnO3 prepared in Example 1 and Comparative Examples 1 and 2 of the present invention; Figure 4 Performance comparison chart of photocatalytic degradation of bisphenol A by AgIn5S8 / LaMnO3, AgIn5S8, and LaMnO3 prepared in Example 1 and Comparative Examples 1 and 2 of the present invention; Figure 5 Photodegradation diagram of the reusability experiment of AgIn5S8 / LaMnO3 prepared in Example 1 of the present invention for photocatalytic degradation of bisphenol A. Detailed implementation mode
[0022] The present invention will be further described in detail below with reference to the accompanying drawings and specific implementation modes.
[0023] Example 1 A synthesis method of a ternary chalcogenide composite perovskite catalytic material, comprising the following steps: A. Add 1 mmol of silver nitrate and 5 mmol of indium chloride to 60 mL of absolute ethanol and continuously stir at 600 r / min for 15 min. Then add 8 mmol of thioacetamide and continue to stir at 600 r / min for 15 min. Subsequently, transfer the solution to a 100 mL polytetrafluoroethylene-lined hydrothermal reaction kettle for hydrothermal reaction, maintain at 160 °C for 24 h, cool to room temperature after the reaction, centrifuge to collect the obtained product, wash it several times with deionized water and absolute ethanol, and then dry it to constant weight in an oven at 60 °C to obtain the material AgIn5S8; B. Dissolve 100 mg of AgIn5S8, 33.6 mg of MnCl2·4H2O, and 63.4 mg of citric acid in 60 mL of distilled water and continuously stir at 600 r / min for 15 min. Then add 69.4 mg of La(NO3)3·6H2O and continue to stir at 600 r / min for 15 min. Heat the solution to 70 °C and continuously stir at 600 r / min for 5 min until a gel-like precursor is obtained. Subsequently, transfer it to a 100 mL polytetrafluoroethylene-lined hydrothermal reaction kettle for hydrothermal reaction, maintain at 210 °C for 18 h. After the reaction, wash it with deionized water and absolute ethanol, filter, and dry it to constant weight in an oven at 60 °C. Finally, calcine the obtained composite material in a box furnace at a heating rate of 2 °C / min to 700 °C for 4 h, and cool it naturally to obtain the catalytic material AgIn5S8 / LaMnO3.
[0024] Figure 1 The scanning electron microscope image of AgIn5S8 / LaMnO3 prepared in this example is as follows. As Figure 1 shown, the AgIn5S8 / LaMnO3 layered nanosheets stack with each other to form a nano-block-like structure, and this compact structure is conducive to the rapid transfer of photogenerated electrons between each other.
[0025] Comparative Example 1, Only prepare AgIn5S8: Add 1 mmol of silver nitrate and 5 mmol of indium chloride to 60 mL of absolute ethanol and continuously stir at 600 r / min for 20 min. Then add 4 mmol of thioacetamide and continue to stir at 600 r / min for 20 min. Subsequently, transfer this solution to a 100 mL polytetrafluoroethylene-lined hydrothermal reaction kettle for hydrothermal reaction, keep it at 200 °C for 20 h. After the reaction is completed, cool it to room temperature, centrifuge to collect the obtained product, wash it several times with deionized water and absolute ethanol, and then dry it to constant weight in an oven at 60 °C to obtain the material AgIn5S8.
[0026] Comparative Example 2, Only prepare LaMnO3: Dissolve 33.6 mg of MnCl2·4H2O and 63.4 mg of citric acid in 60 mL of distilled water and continuously stir at 600 r / min for 30 min. Then add 69.4 mg of La(NO3)3·6H2O and continue to stir at 600 r / min for 30 min. Heat the solution to 80 °C and continuously stir at 600 r / min for 7.5 min until a gel-like precursor is obtained. Subsequently, transfer it to a 100 mL polytetrafluoroethylene-lined hydrothermal reaction kettle for hydrothermal reaction, keep it at 240 °C for 16 h. After the reaction is completed, wash it with deionized water and absolute ethanol, filter it, and dry it to constant weight in an oven at 60 °C. Finally, calcine the obtained composite material in a box furnace, heat it to 600 °C at a rate of 5 °C / min and calcine for 5 h, and then cool it naturally to obtain the catalytic material LaMnO3.
[0027] Example 2, A synthesis method of a ternary chalcogenide composite perovskite catalytic material, comprising the following steps: A. 1 mmol of silver nitrate and 2.5 mmol of indium chloride were added to 60 mL of absolute ethanol and continuously stirred at 600 r / min for 30 min. Then, 4 mmol of thioacetamide was added and stirring was continued at 600 r / min for 30 min. Subsequently, the solution was transferred to a 100 mL Teflon-lined hydrothermal reactor for hydrothermal reaction, maintained at 200 °C for 20 h. After the reaction, it was cooled to room temperature, and the resulting product was collected by centrifugation, washed several times with deionized water and absolute ethanol, and then dried in an oven at 60 °C to constant weight to obtain the material AgIn5S8; B. 100 mg of AgIn5S8, 16.8 mg of MnCl2·4H2O, and 31.7 mg of citric acid were dissolved in 60 mL of distilled water and continuously stirred at 600 r / min for 30 min. Then, 34.7 mg of La(NO3)3·6H2O was added and stirring was continued at 600 r / min for 30 min. The solution was heated to 80 °C and continuously stirred at 600 r / min for 10 min until a gel-like precursor was obtained. Subsequently, it was transferred to a 100 mL Teflon-lined hydrothermal reactor for hydrothermal reaction, maintained at 180 °C for 20 h. After the reaction, it was washed with deionized water and absolute ethanol, filtered, and dried in an oven at 60 °C to constant weight. Finally, the obtained composite material was calcined at high temperature in a box furnace, heated to 600 °C at a rate of 10 °C / min and calcined for 5 h, and then naturally cooled to obtain the catalytic material AgIn5S8 / LaMnO3.
[0028] Example 3 A synthesis method of a ternary chalcogenide composite perovskite catalytic material, comprising the following steps: A. 1 mmol of silver nitrate and 2.5 mmol of indium chloride were added to 60 mL of absolute ethanol and continuously stirred at 600 r / min for 30 min. Then, 8 mmol of thioacetamide was added and stirring was continued at 600 r / min for 15 min. Subsequently, the solution was transferred to a 100 mL Teflon-lined hydrothermal reactor for hydrothermal reaction, maintained at 180 °C for 22 h. After the reaction, it was cooled to room temperature, and the resulting product was collected by centrifugation, washed several times with deionized water and absolute ethanol, and then dried in an oven at 60 °C to constant weight to obtain the material AgIn5S8; B. Dissolve 100 mg of AgIn5S8, 33.6 mg of MnCl2·4H2O, and 31.7 mg of citric acid in 60 mL of distilled water and continuously stir at 600 r / min for 30 min. Then add 69.4 mg of La(NO3)3·6H2O and continue to stir at 600 r / min for 15 min. Heat the solution to 75 °C and continuously stir at 600 r / min for 8 min until a gel-like precursor is obtained. Subsequently, transfer it to a 100 mL polytetrafluoroethylene-lined hydrothermal reaction kettle for hydrothermal reaction, maintain at 240 °C for 16 h. After the reaction, wash with deionized water and absolute ethanol, filter, and dry in an oven at 60 °C to constant weight. Finally, calcine the obtained composite material at high temperature in a box furnace, heat up to 800 °C at a rate of 5 °C / min and calcine for 3 h, and then naturally cool to obtain the catalytic material AgIn5S8 / LaMnO3.
[0029] (I)Photocatalytic degradation performance evaluation Photodegradation experiments of bisphenol A were carried out on the catalytic materials prepared in Example 1 and Comparative Examples 1 and 2 respectively to evaluate the photocatalytic degradation performance of the synthesized AgIn5S8 / LaMnO3 photocatalyst under PMS activation. The specific experiments are as follows: The photocatalytic degradation process was carried out in a customized 250 mL double-walled quartz beaker with a cooling water circulation system to keep the reaction temperature constant. The light source used was a 300 W xenon lamp (420 < λ < 780 nm), and its average light intensity was 200 mW / cm 2 . Before the reaction started, 50 mg of the photocatalyst was dispersed in the bisphenol A solution (10 mg / L, 100 mL), and the pH value was controlled at about 7 with 0.1 M hydrochloric acid or sodium hydroxide solution. The suspension was continuously stirred throughout the reaction. A dark adsorption experiment was carried out for the first 30 minutes before illumination to achieve the adsorption-desorption equilibrium between bisphenol A and the photocatalyst. Then, 1 mM of PMS was added. During the photocatalytic degradation process, 1 mL of the reaction solution was taken out at regular intervals and then passed through a 0.22 μm filter for ultra-high performance liquid chromatography analysis. The mobile phase was acetonitrile and ultrapure water (volume ratio 50:50), and the detection wavelength was 278 nm. The relative concentration (C / C0) was used to calculate the degradation efficiency.
[0030] Figure 2 UV-visible diffuse reflectance absorption spectra of AgIn5S8 / LaMnO3, AgIn5S8, and LaMnO3 prepared in Example 1 and Comparative Examples 1 and 2. As Figure 2As shown, the optical absorption cut-off edges of single AgIn5S8 and LaMnO3 are approximately 688 and 770 nm respectively, which means that both of these single materials can absorb the vast majority of visible light. For the composite material AgIn5S8 / LaMnO3, under the complementary optical absorption of the two, the overall optical absorption of the material is effectively enhanced, while the intensity of the absorption tail peak of the material is retained, and the optical absorption cut-off edge extends to approximately 780 nm, effectively improving the visible light capture efficiency of the composite material.
[0031] Figure 3 FTIR spectra of AgIn5S8 / LaMnO3, AgIn5S8, and LaMnO3 prepared in Example 1 and Comparative Examples 1 and 2. For AgIn5S8, the peaks near 3425 cm -1 , 1339 cm -1 and 1548 cm -1 correspond to the stretching vibrations of hydroxyl groups, and the peak at 525 - 700 cm -1 corresponds to the vibration of the In-S bond in AgIn5S8. For LaMnO3, it can be seen from the FTIR spectrum of pure LaMnO3 that there is a strong absorption band at 610 cm -1 , which is caused by the stretching vibration of the Mn-O bond. For the composite material AgIn5S8 / LaMnO3, it is obvious that the typical characteristic peaks corresponding to AgIn5S8 and LaMnO3 are retained in its FTIR spectrum, indicating the successful synthesis of AgIn5S8 / LaMnO3 and the good preservation of the basic structure after the combination of AgIn5S8 and LaMnO3.
[0032] Figure 4 Performance comparison chart of photocatalytic degradation of bisphenol A by AgIn5S8 / LaMnO3, AgIn5S8, and LaMnO3 prepared in Example 1 and Comparative Examples 1 and 2. As Figure 4 shown, the experimental results show that: under the conditions of a catalyst dosage of 0.5 g / L, an initial concentration of bisphenol A of 10 mg / L, and an initial temperature of room temperature. The degradation efficiencies of bisphenol A in the single AgIn5S8 / PMS and LaMnO3 / PMS systems within 25 min are 46.38% and 64.42% respectively, which indicates that the single material systems have a certain degradation efficiency for BPA under visible light irradiation. However, due to the narrow bandgap leading to a relatively high recombination rate of bulk carriers, the photo-generated electrons cannot be effectively utilized. The removal rate of bisphenol A in the AgIn5S8 / LaMnO3 / PMS system reaches 95.84%, which means that the S-type heterojunction constructed by two materials with mutually matching energy band structures effectively improves the interfacial charge transfer of photo-generated carriers and inhibits the in-situ recombination of photo-generated electron-hole pairs in the two single photocatalysts.
[0033] (II) Continuous degradation experiment After the first degradation reaction of the AgIn5S8 / LaMnO3 prepared in Example 1 was completed, the reaction solution was centrifuged and washed. The recovered catalyst was dried in a freeze dryer for 48 h, and then put into the reactor again for the next degradation experiment. Except for the material, the remaining degradation reaction conditions and the experimental setup procedure for the first photocatalytic degradation performance evaluation were kept consistent; after the second reaction was completed, the above steps were repeated for three degradation experiments.
[0034] Figure 5 It is the degradation diagram of the reusability experiment of the AgIn5S8 / LaMnO3 photocatalytic degradation of bisphenol A prepared in Example 1. As Figure 5 shown, the degradation efficiency of bisphenol A was above 85% in three consecutive degradation experiments, indicating that the photocatalytic activity of the AgIn5S8 / LaMnO3 photocatalytic nanomaterial remained good after three cycles.
Claims
1. A method for synthesizing a ternary chalcogenide composite perovskite catalytic material, characterized in that It includes the following steps: A. Add silver nitrate and indium chloride into absolute ethanol and continuously stir. Then add thioacetamide and continue stirring. Subsequently, conduct a hydrothermal reaction on this solution. After the reaction ends, cool it to room temperature, centrifuge to collect the obtained product, wash it, and then dry it to a constant weight to obtain the material AgIn5S8; B. Dissolve AgIn5S8, MnCl2·4H2O, and citric acid in distilled water and continuously stir. Then add La(NO3)3·6H2O and continue stirring. Heat this solution and continuously stir until a gel-like precursor is obtained. Subsequently, conduct a hydrothermal reaction. After the reaction ends, wash it, filter it, and dry it to a constant weight. Finally, calcine the obtained composite material and let it cool naturally to obtain the catalytic material AgIn5S8 / LaMnO3.
2. The synthesis method of a ternary chalcogenide composite perovskite catalytic material according to claim 1, characterized in that: In step A, the molar ratio of silver nitrate, indium chloride, and thioacetamide is 1:2.5 - 5:4 - 8.
3. The synthesis method of a ternary chalcogenide composite perovskite catalytic material according to claim 1, characterized in that: In step A, the temperature of the hydrothermal reaction is 160 - 200 °C, and the time of the hydrothermal reaction is 20 - 24 h.
4. The synthesis method of a ternary chalcogenide composite perovskite catalytic material according to claim 1, characterized in that: In step B, the mass ratio of AgIn5S8, MnCl2·4H2O, citric acid, and La(NO3)3·6H2O is 100:16.8 - 33.6:31.7 - 63.4:34.7 - 69.
4.
5. The synthesis method of a ternary chalcogenide composite perovskite catalytic material according to claim 1, characterized in that: In step B, the heating temperature is 70 - 80 °C, and the continuous stirring time is 5 - 10 min.
6. The synthesis method of a ternary chalcogenide composite perovskite catalytic material according to claim 1, characterized in that: In step B, the temperature of the hydrothermal reaction is 180 - 240 °C, and the time of the hydrothermal reaction is 16 - 20 h.
7. The synthesis method of a ternary chalcogenide composite perovskite catalytic material according to claim 1, characterized in that: In step B, during calcination, the heating rate is 2 - 10 °C / min, the calcination temperature is 600 - 800 °C, the calcination time is 3 - 5 h, and the atmosphere is air.
8. A ternary chalcogenide composite perovskite catalytic material, characterized in that: It is prepared by the synthesis method of the ternary chalcogenide composite perovskite catalytic material described in any one of claims 1 - 7.
9. The application of a ternary chalcogenide composite perovskite catalytic material according to claim 8 in photocatalytic degradation of pollutants.
10. Use of a ternary chalcogenide composite perovskite catalytic material according to claim 9 in photocatalytic degradation of pollutants, characterized in that: The pollutants include bisphenol A.
Citation Information
Patent Citations
Method for preparing quaternary sulfide quantum dot based heterojunction efficient photocatalyst
CN105727999A
Preparation method and application of indium silver sulfide
CN112058280A
Perovskite solar cell based on transition metal sulfide / ternary sulfide quantum dot composite hole transport layer and preparation method of perovskite solar cell
CN113178506A
Novel iron-nickel-sulfur-based heterojunction catalytic material as well as preparation method and application thereof
CN118950034A
Method for degrading bisphenol A by using lanthanum manganate catalyst rich in oxygen vacancies
CN119034721A